Food insecurity and coping strategies in a marine protected area in southeastern Tanzania. Issue 3 (4th May 2018) - Kamat, Vinay R.; Woo Kinshella, Mai-Lei
ABSTRACT: This article examines the perceived food security and coping strategies in coastal communities located in a marine protected area (MPA) in southeastern Tanzania. Drawing on fieldwork concentrated in a representative coastal village, the article illustrates how women in particular understand their food security situation in relation to the MPA. Data from interviews with 120 women suggest that the majority of the households in the study area were food insecure. Only few respondents, however, specifically attributed their food insecurity to the MPA's presence in their village, suggesting that food security is multidimensional and is undergirded by several interrelated factors that vary over time. The findings query the assertion that MPAs can and do contribute to improved food security in coastal populations through increased fish biomass or ecotourism projects.